2023
DOI: 10.1093/nutrit/nuad141
|View full text |Cite
|
Sign up to set email alerts
|

Changes in energy and macronutrient intakes during Ramadan fasting: a systematic review, meta-analysis, and meta-regression

Dana N Abdelrahim,
Salah Eddine El Herrag,
Meghit Boumediene Khaled
et al.

Abstract: Context Ramadan fasting (RF) is associated with various physiological and metabolic changes among fasting Muslims. However, it remains unclear whether these effects are attributable to changes in meal timing or changes in dietary energy and macronutrient intakes. Furthermore, the literature on the associations between RF, meal timing, and energy and macronutrient intakes is inconclusive. Objectives This systematic review aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
0
0
0
Order By: Relevance
“…Our results showed that RIF was not associated related to variations in total daily caloric intake at different timepoints, which is consistent with previous studies among female athletes ( 5 , 18 , 52 , 53 ). Similarly, Abdelrahim et al ( 54 ) indicated that the different physiological and health effects associated with RIF may be explained by changes in meal timing rather than by changes in quantitative dietary intake. Nevertheless, Jahrami et al ( 41 ) suggested that RIF might be linked to a significant, small decrease in body weight in young, healthy, non-athletic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that RIF was not associated related to variations in total daily caloric intake at different timepoints, which is consistent with previous studies among female athletes ( 5 , 18 , 52 , 53 ). Similarly, Abdelrahim et al ( 54 ) indicated that the different physiological and health effects associated with RIF may be explained by changes in meal timing rather than by changes in quantitative dietary intake. Nevertheless, Jahrami et al ( 41 ) suggested that RIF might be linked to a significant, small decrease in body weight in young, healthy, non-athletic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, reported studies are inconsistent on the intake of macronutrients, including fat ( 3 , 14 , 19 ), carbohydrates ( 13 , 17 , 19 ), cholesterol ( 13 , 14 ), and protein ( 3 , 19 ). Recently, Abdelrahim et al conducted a meta-analysis and reported a reduction in total energy intake, carbohydrates, protein and water intakes and no change in fat or protein intakes during Ramadan ( 4 ). The previous observational studies often focused on specific ethnic groups or nationalities, potentially skewing the results.…”
Section: Introductionmentioning
confidence: 99%
“…Ramadan intermittent fasting (RIF) is associated with a sudden drastic change in the dietary behavior of observers. Although observing RIF does not dictate restriction on calorie intake or type of food, previous studies showed that it incurs significant changes in eating habits, patterns, duration, frequency of meals and intakes of energy and macronutrients (1)(2)(3)(4). Observers feast after sunset (Iftar) and eat another lighter meal before dusk (Suhur) (5) and more often in groups of family and friends (6).…”
Section: Introductionmentioning
confidence: 99%